The design of an air compressor - Bobbitt, Fred Winchester (My University, 1900)
Introduction: The machine of which the plates herewith attached are the assembled drawings is to be a Nine horse -power, Belt -driver Air Compressor designed to discharge fifty cubic feet of free air per minute, at a maximum pressure of 100 pounds per square inch. It is to be of the vertical type, with two single acting cylinders. The machine is to be run at one hundred and twenty revolutions per minute, with an eight inch stroke. Each cylinder compresses the air to the pressure in the reservoir, and delivers directly into the discharge pipe.
Citation: Bobbitt, Fred Winchester. The design of an air compressor. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Belt driver air compressors; Piston displacement; Horse power; Cylinder volume; Theses